The Impact of Anxiety and Depression on Academic Performance: A Cross-Sectional Study among Medical Students in Syria - Jamil, Hasan; Alakkari, Mohab; Al-Mahini, Mohammed Saleem; Alsayid, Muhammad; Al Jandali, Omar (Avicenna Journal of Medicine, 2022)
Background The National Medical Unified Examination (NMUE) is a milestone in the life of medical students in Syria. The selection for residency programs depends mainly on the NMUE score, where competitive specialties require higher scores. Therefore, preparation for the NMUE might be a source of anxiety and depression. This study aims at evaluating the impact of anxiety and depression on the NMUE score. A secondary objective is to determine the effect of some factors (i.e., exercise, having breakfast, adequate sleep, and social media) on anxiety and depression.Methods A cross-sectional study was conducted using an online questionnaire and included medical students who were preparing for the October 2019 NMUE exam. The Generalized Anxiety Disorder scale (GAD-7) and the Patient Health Questionnaire (PHQ-9) were used to screen for anxiety and depression, respectively. NMUE scores were obtained from the official score report. Demographics and other potential confounding factors, such as Cumulative Grade Point Average, were obtained through the questionnaire.Results One hundred and thirty (n = 130) students participated in the study, 83 of them were women (63.8%). The prevalence of anxiety and depression were 59.2 and 58%, respectively, with no difference between men and women. Both anxiety and depression were negatively correlated with the NMUE score. However, this relationship did not persist after controlling for other important predictors through multiple regression. Only exercising was statically significant in reducing PHQ-9 scores. None of the studied factors were significant in reducing GAD-7 scores.Conclusion Although participants with higher anxiety/depression had lower NMUE scores, this association does not imply causation. The high prevalence of anxiety and depression (approximately two-thirds of the participants) is concerning and may pose a great threat to students' well-being and adversely affect the quality of care provided by them as future health care professionals.
Keywords: anxiety; depression; academic performance; National Medical Unified Examination; medical students; university